Catecholaminergic activity among young adults after high phosphorus intake during childhood and adolescence - Franco, Luciana Peixoto; Derakhshandeh-Rishehri, Seyedeh-Masomeh; Nöthlings, Ute; Kalhoff, Hermann; Peitzsch, Mirko; Wudy, Stefan A.; Remer, Thomas (Hormones (Athens, Greece), 2025)
Elevated catecholamine secretion has been reported after high dietary phosphate intake in experimental studies in animals and humans. This study thus aimed to examine the prospective relationship between long-term dietary phosphorus intake during childhood and adolescence-assessed via 24-h urinary phosphate excretion-and catecholamine levels in adulthood. A total of 159 healthy participants of the DONALD Study (Dortmund, Germany) were examined, who had repeatedly provided 24-h urine samples between ages 3 and 17 years and from whom a 24-h specimen was collected again in young adulthood (ages 18-35). In the adult samples, urinary free epinephrine (EPI), norepinephrine (NE) and the O-methylated EPI- and NE-metabolites metanephrine and normetanephrine were quantified using LC-MS/MS. Phosphate was measured ion chromatographically. Individual means of standard deviation scores were calculated for urinary phosphate and further biomarker excretions as well as for anthropometric data longitudinally determined between 3 and 17 years. Multivariable linear regression was used to investigate associations between pre-adulthood phosphate and adult catecholamine excretions. After fully adjusting for growth- and adulthood-related covariates, only females' renal excretions of EPI (p=0.030) and NE (p=0.040) were associated significantly with pre-adulthood phosphate excretion. In line with a disease-free, relatively continuous adrenal-medullary production of O-methylated metabolites, no association at all was seen for metanephrine and normetanephrine. Our study provides biomarker-based evidence that habitual high dietary phosphorus intake during childhood and adolescence may be related to elevated catecholaminergic activity in adulthood, at least in females, potentially contributing in the long term to endocrine-metabolic-related neuronal and cardiovascular disorders.